Accuracy of the planar compliant mechanisms (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2008)
In the recent years a class of devices called compliant mechanisms is in the focus of many investigations. Their use in the design of modern devices, especially in micro-electro-mechanical systems (MEMS), is inevitable because of the difficulty in fabricating rigid-body joints and assembling parts. Compliant mechanisms rely upon elastic deformation to perform their function of transmitting and/or transforming motion and force. Flexural pivot-based designs use narrow sections connecting relative\-ly rigid segments. Thus, compliance is lumped to a few portions of the mechanism. The introduction of the elastic pivots instead of the rigid-body joints leads to certain deviations in the performance of the compliant mechanisms compared with the analo\-gous rigid-body linkages. These deviations are the object of study in the paper. Based on the graph theory, a method for effective estimation of the accuracy of compliant mechanisms with flexural pivots is elaborated and practical examples are considered.